2007
DOI: 10.1016/j.snb.2006.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic pumping in nuclear magnetic resonance environments

Abstract: We present a DC magnetohydrodynamic (MHD) pump as component of a nuclear magnetic resonance (NMR) microfluidic chip. This is the first time that MHD pumping in an NMR environment was observed and demonstrated. This chip generates a maximum flow rate of 1.5 L min −1 (2.8 mm s −1 in the microchannel) for an applied voltage of 19 V with only 38 mW of power consumption in a 7 T superconductive magnet. We developed a simple method of flow rate measurement inside the bulky NMR magnet by monitoring the displacement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…MHD pumps with the highest body force are obtained when the current density, magnetic field intensity and electrode length are maximized (by minimizing the cross-sectional area). In an NMR environment, this pump by Homsy et al (2007) was shown to perform the best as compared to other MHD pumps under such operating conditions but the superconductive magnet used was several feet high.…”
Section: Magnetohydrodynamic Pumpsmentioning
confidence: 94%
See 1 more Smart Citation
“…MHD pumps with the highest body force are obtained when the current density, magnetic field intensity and electrode length are maximized (by minimizing the cross-sectional area). In an NMR environment, this pump by Homsy et al (2007) was shown to perform the best as compared to other MHD pumps under such operating conditions but the superconductive magnet used was several feet high.…”
Section: Magnetohydrodynamic Pumpsmentioning
confidence: 94%
“…For laminar flow, the maximum flow rate can be obtained by ( Several MHD pumps in the literature were compared against a recent MHD pump designed for use in a nuclear magnetic resonance (NMR) environment by Homsy et al (2007).…”
Section: Magnetohydrodynamic Pumpsmentioning
confidence: 99%
“…The electric field is applied through a small gap connecting the reservoirs with electrodes and the flow channel. To increase the flow rate, Homsy et al (2007) used a strong magnet of 7 Tesla. A linear relationship between the flow rate and the applied voltage was found.…”
Section: Electrically Conducting Fluidsmentioning
confidence: 99%
“…The application of MHD to weakly conductive electrolyte solutions is somewhat more complicated due to electrodes' electrochemistry. Recently, various MHD-based microfluidic devices including micro-pumps (Jang and Lee, 2000; Lemoff and Lee, 2000; Huang et al, 2000; Bau, 2001; Zhong et al, 2002; Bau et al, 2002, 2003; Sawaya et al, 2002; West et al, 2002, 2003; Ghaddar and Sawaya, 2003; Bao and Harrison, 2003a, 2003b; Eijkel et al, 2004; Wang et al, 2004; Arumugam et al, 2004, 2006; Qian and Bau, 2005b; Homsy et al, 2005, 2007; Affanni and Chiorboli, 2006; Aguilar et al, 2006; Kabbani et al, 2007; Patel and Kassegne, 2007; Duwairi and Abdullah, 2007; Ho, 2007), stirrers (Bau et al, 2001; Yi et al, 2002; Qian et al, 2002; Gleeson and West, 2002; Xiang and Bau, 2003; Gleeson et al, 2004; Qian and Bau, 2005a), networks (Bau et al, 2002, 2003), heat exchangers (Sviridov et al, 2003; Singhal et al, 2004; Duwairi and Abdullah, 2007), and analytical and biomedical devices (Leventis and Gao, 2001; West et al, 2002, 2003; Bao and Harrison, 2003a; Lemoff and Lee, 2003; Eijkel et al, 2004; Clark and Fritsch, 2004; Homsy et al, 2007; Gao et al, 2007; Panta et al, 2008) operating under either DC or AC electric fields have been designed, modeled, constructed, and tested. The DC operation is often adversely impacted by the electrodes' electrochemistry leading to bubble formation and electrode corrosion.…”
Section: Introductionmentioning
confidence: 99%